The hydrodynamic structure of a methane-air tulip flame - Kaltayev, A. K.; Riedel, Uwe; Warnatz, Jürgen (Combustion science and technology, 2007)
The flame propagation and structure of a stoichiometric methane-air flame in a closed vessel is investigated. For the parameter range examined a tulip flame is formed. A qualitative agreement with experiments is obtained for different length to width ratios of the vessel. The results indicate an enhanced tulip effect with increasing vessel length.